From L2 interactional competence to L2 interactional repertoires: reconceptualising the objects of L2 learning. Issue 1 (2nd January 2018) - Hall, Joan Kelly
Abstract: In this paper, I offer a reconsideration of interactional competence as an object of L2 learning. I argue that the field's uptake of the concept displays a misunderstanding of, or at least a lack of attention to, its related but distinct intellectual roots in linguistic anthropology and conversation analysis. This has resulted in conceptual confusion in studies that draw mainly on conversation analysis to examine L2 learning. I offer interactional repertoires as a more empirically useful concept to capture the objects of L2 learning. Its usefulness is twofold. First, it more aptly captures the variable nature of the multilingual, multimodal resources that learners draw on and develop in their diverse contexts of use. Second, it suggests a more empirically valid understanding of learning, not as a linear, single, one-path-fits-all process, but rather as multidimensional trajectories occurring over L2 learners' lifespans.